The Effect of Age Diversity in Groups on Peer Evaluations and Individual Performance - Katja Görlitz; Tim Sels (Kyklos, 2025)
This study analyzes how individuals evaluate their peers' performance in a high-stakes tournament in response to being randomly assigned to an age homogenous or heterogenous group using data from two TV shows. The data also allow us to explore expert evaluations because it contains objective ratings from an independent expert. Additionally, this study investigates how age-diverse groups affect individual performance in professional golf tournaments. The results show that peer and expert evaluations as well as individual performance are lower in age-diverse groups. Further evidence suggests that these effects occur when group members are unfamiliar but fade away once group members have gotten to know each other.
Keywords: 300; Age diversity; expert evaluation; peer evaluation; performance